Co-simulation framework of discrete element method and multibody dynamics models. Issue 3 (8th May 2018) - Lommen, Stef; Lodewijks, Gabriel; Schott, Dingena L.
Abstract : Purpose: Bulk material-handling equipment development can be accelerated and is less expensive when testing of virtual prototypes can be adopted. However, often the complexity of the interaction between particulate material and handling equipment cannot be handled by a single computational solver. This paper aims to establish a framework for the development, verification and application of a co-simulation of discrete element method (DEM) and multibody dynamics (MBD). Design/methodology/approach: The two methods have been coupled in two directions, which consists of coupling the load data on the geometry from DEM to MBD and the position data from MBD to DEM. The coupling has been validated thoroughly in several scenarios, and the stability and robustness have been investigated. Findings: All tests clearly demonstrated that the co-simulation is successful in predicting particle–equipment interaction. Examples are provided describing the effects of a coupling that is too tight, as well as a coupling that is too loose. A guideline has been developed for achieving stable and efficient co-simulations. Originality/value: This framework shows how to achieve realistic co-simulations of particulate material and equipment interaction of a dynamic nature.